Ret and Substrate-Derived TGF-β Maverick Regulate Space-Filling Dendrite Growth in Drosophila Sensory Neurons - Hoyer, Nina; Zielke, Philip; Hu, Chun; Petersen, Meike; Sauter, Kathrin; Scharrenberg, Robin; Peng, Yun; Kim, Charles C.; Han, Chun; Parrish, Jay Z.; Soba, Peter (Cell Reports, 2018)
Dendrite morphogenesis is a highly regulated process that gives rise to stereotyped receptive fields, which are required for proper neuronal connectivity and function. Specific classes of neurons, including Drosophila class IV dendritic arborization (C4da) neurons, also feature complete space-filling growth of dendrites. In this system, we have identified the substrate-derived TGF-β ligand maverick (mav) as a developmental signal promoting space-filling growth through the neuronal Ret receptor. Both are necessary for radial spreading of C4da neuron dendrites, and Ret is required for neuronal uptake of Mav. Moreover, local changes in Mav levels result in directed dendritic growth toward regions with higher ligand availability. Our results suggest that Mav acts as a substrate-derived secreted signal promoting dendrite growth within not-yet-covered areas of the receptive field to ensure space-filling dendritic growth. Hoyer et al. uncover a mechanism for space-filling dendrite growth in vivo. Substrate-derived TGF-β Maverick and the Ret receptor together regulate the dendrite growth and stability of Drosophila sensory neurons. They show that Ret is required for uptake of Maverick, whose local levels determine dendrite growth preference.
CRIS-Team Scopus Importer:2021-11-16
Keywords: cell surface receptor; dendrite morphogenesis; dendrite-substrate interaction; Drosophila sensory neurons; receptive field; receptor tyrosine kinase; Ret receptor; space-filling dendrite growth; TGF-β